2016
DOI: 10.1371/journal.pone.0163752
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adolescent Intermittent Alcohol Exposure on the Expression of Endocannabinoid Signaling-Related Proteins in the Spleen of Young Adult Rats

Abstract: Intermittent alcohol exposure is a common pattern of alcohol consumption among adolescents and alcohol is known to modulate the expression of the endocannabinoid system (ECS), which is involved in metabolism and inflammation. However, it is unknown whether this pattern may have short-term consequences on the ECS in the spleen. To address this question, we examined the plasma concentrations of metabolic and inflammatory signals and the splenic ECS in early adult rats exposed to alcohol during adolescence. A 4-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…Various data indicated that the liver cells were damaged, which is consistent with the result of a discovery in HE dyeing of zebrafish larvae liver, where the liver suffered from lesion of different degrees. These results were also agreed by previous studies, where spontaneous activities were suppressed due to high-concentration ethanol [28], causing metabolic abnormality and tissue injury [2930].…”
Section: Discussionsupporting
confidence: 93%
“…Various data indicated that the liver cells were damaged, which is consistent with the result of a discovery in HE dyeing of zebrafish larvae liver, where the liver suffered from lesion of different degrees. These results were also agreed by previous studies, where spontaneous activities were suppressed due to high-concentration ethanol [28], causing metabolic abnormality and tissue injury [2930].…”
Section: Discussionsupporting
confidence: 93%
“…It is thus possible that the pattern displayed by the adolescent rats, in the DID-like section of the present study, may reflect a normative decrease in ethanol acceptance, as the animals transition from adolescence to adulthood. It is worth noting that, during the course of the protocol, we employed increasing concentrations of alcohol (from 8 to 10%), yet these were still lower than those employed in other DIDlike procedures [e.g., 20% (Pavon et al, 2016)]. Perhaps different ethanol self-administrations patterns would have been observed had we employed higher ethanol concentrations, or had we kept the ethanol concentration stable across sessions.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study we will present data from the 12 litters regarding alcohol intake; four litters remained intact and were devoted to a different study. The other eight litters were used for the behavioral analysis, blood samples were collected, and at sacrifice, half of the brains were collected and employed in this study for western blot analysis, while the remaining animals were dedicated to another study which results have been already published (Pavón et al, 2016 ). Therefore, these neurobiological data come from animals previously submitted to behavioral analysis.…”
Section: Methodsmentioning
confidence: 99%